Computer-based oral exams in Italian language studies - Newhouse, C.; Cooper, Martin (Cambridge University Press, 2013)
In this paper we report on one component of a three-year study into the use of digital technologies for summative performance assessment in senior secondary courses in Western Australia. One of the courses was Italian Studies, which had an oral communication outcome externally assessed with an oral performance for which students travelled to a central location and undertook an interview with two assessors. Apart from the logistical difficulties for both students and the organising body, this method did not leave an enduring record of the process, and raised questions about the reliability of the assessment. Over the three years of this study, we tried several approaches to using digital technology to assess oral performance, including a portfolio of sub-tasks leading up to a video-recorded oral presentation, a computer-based exam, a video recorded interview, and an online exam that included oral audio-recordings. For each of the years online marking tools supported two methods of drawing inferences about student performance from the representations: the more traditional analytical method and the comparative pairs method. Rasch analysis of the results of the two methods showed that both were at an acceptable level of reliability. Overall, students and teachers reported that they liked using audiovisual recordings and online performance tasks for revision but not for summative assessment. The study also demonstrated that the scores from externally marked computer-based oral tasks carried out in class time correlated highly with the scores from traditional face-to-face recorded interviews. Therefore, online assessment of oral performance appears to be an equally effective way to facilitate assessment when compared with traditional methods and offers other affordances, such as convenience and access from a variety of locations, as well as providing an enduring record of student performance.